Takefumi Aida : Toy Block House III, Tokyo, 1980-81
Se desarrolla la obra Toy Block House III del arquitecto japonés Takefumi Aida.
Keywords: AIDA, TAKEFUMI; JAPON; TOKYO; VIVIENDAS; VIVIENDAS UNIFAMILIARES